2023
DOI: 10.1039/d2ay01175a
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymers as effective capturing receptors in a pseudo-ELISA immunoassay for procalcitonin detection in veterinary species

Abstract: In this study, a new sandwich-type immunoenzymatic assay, based on a molecularly imprinted polymer (MIP) as an artificial antibody (pseudo-ELISA), was developed for the determination of procalcitonin (PCT) in veterinary...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Similarly, MIPs can be imprinted with bone loss biomarkers incorporated with quantum dots to help monitor bone activity. Battaglia et al demonstrated that MIPs can be used in pseudo-ELISA immune assays by replacing the capture antigen with imprinted procalcitonin on a (polynorepinephrine)-based polymer and proved that it can be a viable technique . Various ways in which MIPs can be incorporated into sensing are represented in Figure .…”
Section: Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%
“…Similarly, MIPs can be imprinted with bone loss biomarkers incorporated with quantum dots to help monitor bone activity. Battaglia et al demonstrated that MIPs can be used in pseudo-ELISA immune assays by replacing the capture antigen with imprinted procalcitonin on a (polynorepinephrine)-based polymer and proved that it can be a viable technique . Various ways in which MIPs can be incorporated into sensing are represented in Figure .…”
Section: Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%